2017
DOI: 10.1371/journal.pone.0183693
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-associated metabolic syndrome spontaneously induces infiltration of pro-inflammatory macrophage in synovium and promotes osteoarthritis

Abstract: ObjectivesEpidemiological and experimental studies have established obesity to be an important risk factor for osteoarthritis (OA), however, the mechanisms underlying this link remains largely unknown. Here, we studied local inflammatory responses in metabolic-OA.MethodsWistar rats were fed with control diet (CD) and high-carbohydrate, high-fat diet (HCHF) for period of 8 and 16 weeks. After euthanasia, the knees were examined to assess the articular cartilage changes and inflammation in synovial membrane. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 82 publications
2
72
0
3
Order By: Relevance
“…Obesity‐induced systemic and local inflammation plays an important role in the progression of OA damage. The results of the present study and other previous studies have shown that immune cells colocalize within the knee joint during obesity‐induced OA . In addition, the systemic proinflammatory milieu has been shown to be important in the pathogenesis of OA, potentially through interactions with local injury‐induced inflammation .…”
Section: Discussionsupporting
confidence: 79%
“…Obesity‐induced systemic and local inflammation plays an important role in the progression of OA damage. The results of the present study and other previous studies have shown that immune cells colocalize within the knee joint during obesity‐induced OA . In addition, the systemic proinflammatory milieu has been shown to be important in the pathogenesis of OA, potentially through interactions with local injury‐induced inflammation .…”
Section: Discussionsupporting
confidence: 79%
“…Controlling metabolic comorbidities may have a beneficial effect on osteoarthritis, especially in obese patients [232][233][234].…”
Section: Muscle Aging and Gut Microbiotamentioning
confidence: 99%
“…Neben den klassischen PrĂ€arthrose-Faktoren werden in der Literatur als Risikofaktoren u. a. genannt: ▄ Übergewicht [19], ▄ peridontale Erkrankungen [20], ▄ papulopustulöse Hautinfektionen einschl. der SAPHO-Syndrome [21], ▄ Dysbalance der reaktiven oxygenen und nitrogenen [18]…”
Section: Zkm Praxis Neuraltherapieunclassified